STUDI LITERATUR PERAN PEMBIAYAAN PERBANKAN SYARIAH DALAM PEMBERDAYAAN UMKM DI INDONESIA PADA MASA COVID 19 - Arpizal Arpizal; Andri Soemitra (HUKUMAH: Jurnal Hukum Islam, 2022)
The role of Islamic banks in empowering MSMEs in Indonesia has been proven in variousstudies. However, whether Islamic banks still play a role in empowering MSMEs during theCOVID-19 pandemic is a question in this study. This literature study aims to answer researchquestions by describing the role of Islamic banks in empowering MSMEs during the COVID-19 pandemic in Indonesia. Data from 60 articles that have been analyzed with the results ofmapping the four main themes contained in the article. There are 36 articles that support thefact that Islamic banks play an active role in empowering MSMEs during the covid 19 period.The role of Islamic banks in empowering MSMEs is through financing that is carried out byproviding various payment facilities and relaxation. Besides that, Islamic banks also provideassistance by providing knowledge about how to develop business innovation, product qualityin the face of the covid 19 pandemic.